Implementasi Program Presensi Mahasiswa Dengan Menggunakan Face Recognition - Richard Lawrence Thiosdor; Kartika Gunadi; Lily Puspa Dewi (Jurnal Infra, 2021)
The problem of using a physical attendance list causes a cheat where the student does “fake attendance” by asking another students to sign the attendance list on his/her behalf. This problems are often found in college activities.Detection of student faces uses the Face Recognition library as a mean of validation in the attendance check process. Face recognition requires face images that have been preprocessed and uses the K-Nearest Neighbor model (KNN) or Support Vector Machine (SVM) to validate student faces in the attendance check process.Testing on 15 sample face images with 40 total face classes yields an average accuracy of 99%. Face Recognition cannot detect faces if the facial features are obstructed. This validation of student attendance successfully uses Face Recognition to minimize cheating in taking attendance.